The relationship between parental perceptions of transition practices, school readiness and mental health in Chinese children: the moderating effects of sociodemographic factors - Catalina Sau Man Ng; Victor C. W. Chan; Olivier Marchal (Frontiers in Pediatrics, 2026)
Objective Transitioning from kindergarten to primary school (K–P) represents a pivotal milestone in children's development. This study examined relationships among parental perceptions of transition practices, children's school readiness, and mental health outcomes, while exploring the moderating role of sociodemographic factors. Methods Cross-sectional data were collected from 259 Chinese parents through a two-stage sampling process. In the first stage, primary schools were stratified by region (Hong Kong Island, Kowloon, and the New Territories), and a random sample of 21 schools selected from the Education Bureau's official list. In the second stage, parents were recruited within these schools based on consent and eligibility, constituting a convenience sample. Parents completed standardized questionnaires assessing sociodemographic characteristics, perceived effectiveness of transition practices, school readiness, and child mental health. Regression analyses examined associations among these variables. Results Mothers reported higher school readiness scores than fathers. Parental perceptions of curriculum- and administration-focused transition practices were positively associated with multiple school readiness subscales, whereas home–school collaboration practices were linked only to self-management. Emotional and behavioral development emerged as the strongest predictor of reduced depression and anxiety symptoms. Moderation analyses indicated stronger associations between curriculum- and administration-focused practices and general preparedness among low-income families and parents with secondary education or below. Sensitivity analyses using bootstrapping confirmed the robustness of these findings. After Bonferroni corrections, only the interaction between general preparedness and parent gender in predicting mental health outcomes remained significant. Conclusions Findings underscore the importance of tailoring transition practices to the needs of socioeconomically disadvantaged families to promote equitable school readiness and mental health outcomes.